PREDICTION OF FUNCTION TAGS OF THE SIMPLE TURKISH SENTENCES BY CONDITIONAL RANDOM FIELDS - Aygul, Mustafa; Karaalioglu, Gurkan; Amasyali, M. Fatih (YILDIZ TECHNICAL UNIV, 2014)
The prediction of function tags is a key component of several natural language tasks. In this study, Conditional Random Fields are employed for Turkish sentences. The affects of the size of training set, the usage of morphological features of the words are investigated. As a result, we achieved 75% success ratio on our datasets having 2000 simple sentences.
Keywords: Natural language processing; dependency parsing; artificial intelligence; sequence labeling; conditional random fields; Engineering